Open Access to Books – the Perspective of a Non-profit Infrastructure Provider - Eelco Ferwerda; Niels Stern; Ronald Snijder (Journal of Electronic Publishing)
This article describes the open access (OA) book platforms OAPEN Library and Directory of Open AccessBooks (DOAB), based on 1.the development and activities of OAPEN in the first ten years; 2. the underlying technical approach behind the platforms; 3. the current role of OAPEN and DOAB and future outlook.OAPEN started out as a project funded by the European Commission, and become a legal non-profit Dutch entity in 2011. It hosts, disseminates and preserves open access books. OA book publishing has been explored in several pilot projects. Its current collection contains over 24,000 documents. DOAB launched in 2012, inspired and supported by DOAJ. It became a legal non-profit Dutch entity in 2019, owned by the OAPEN Foundationand OpenEdition. It’s current collection contains close to 60,000 titles.The data model of both platforms  is optimised for a multilingual collection and supports funding information. Ingesting books has been optimised to support a wide array of publishers and the dissemination of books takes into account search engines; libraries and aggregators and other organisations. The usage has grown in the last years, to 1 million downloads per month.The future developments entail increased support of research funders with the establishment of a FunderForum and multi-year research into policy development. DOAB will invest more in bibliodiversity, by adding more emphasis on African and Asian countries. Also,DOAB will roll out its Peer Review Information Service for Monographs (PRISM).OAPEN and DOAB will continue to work on developing reliable infrastructures, policy development and quality assurance around open access books.